Economic Development and the Spread of Diseases of Affluence in EU Regions - Żółtaszek, Agata; Olejnik, Alicja (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Diseases of affluence (diseases of the twenty‑first century, Western diseases) by definition should have higher prevalence and/or mortality rates in richer and more developed countries than in poorer, underdeveloped states. Therefore, it has been indicated that it is the civilizational progress (directly or indirectly via changes in lifestyle, diet, physical activity, stress, etc.) that stimulates epidemic outbreaks of some illnesses (cancer, diseases of respiratory and cardiovascular systems, diabetes, mental disorders). On the other hand substantial financial resources, highly qualified medical personnel, and cutting‑edge technology of richer states, should allow for effective prevention, diagnostics, and treatment of these diseases. The European Union as a whole, as well as all its member states and their regions, may be considered “highly developed” in terms of economy. Does it, however, mean that EU can be perceived as homogeneous as far as the diseases of affluence epidemiology is concerned? Are the relatively small differences in economic regional development (compered to worldwide inequalities) a significant factor in the spatial distribution of the diseases of affluence? To evaluate the possible dispersion in the epidemiology of some of the so called Western diseases and their relation to regional development, tools of spatial statistics have been incorporated. The research covers 261 EU NUTS 2 regions for the years 2003–2010. This research may provide some insight into the existence of hypothetical diseases of affluence as well as help recognize spatial patterns of prevalence and mortality rates for these illnesses.